2021
DOI: 10.15789/1563-0625-dpo-2334
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of HLA-A<sup>*</sup>, B<sup>*</sup>, DRB1<sup>*</sup> allele groups among persons who underwent COVID-19

Abstract: The main histocompatibility complex — HLA system (Human Leukocyte Antigens) is among the most important genetic factors determining response of humans to infectious agents. The key role that HLA molecules play in immune response is to present the pathogen-derived peptides. Enormous molecular variability of HLA alleles in human populations have attracted close attention and became the basis for numerous studies aimed at evaluating the role of HLA genotypes for individual features of immune response to COVID-19,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…Our data did not confirm previously published data regarding the association of HLA-A*01:01 with severe COVID-19, neither in Russians nor European population [11] , [17] . On the contrary, our results suggest the HLA-A*01:01 allele might be protective against COVID - 19 and severe symptoms.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our data did not confirm previously published data regarding the association of HLA-A*01:01 with severe COVID-19, neither in Russians nor European population [11] , [17] . On the contrary, our results suggest the HLA-A*01:01 allele might be protective against COVID - 19 and severe symptoms.…”
Section: Discussioncontrasting
confidence: 99%
“…In the residents of the north-western part of Russia (Leningrad region), it was found that allele groups A*02 and A*26 decrease the probability of COVID - 19 infection and A*29 predisposes to the disease. HLA haplotypes that included allele group A*02 were less frequent in COVID - 19 patients, while in the general population these haplotypes are present at a much higher frequency [11] .…”
Section: Introductionmentioning
confidence: 80%